Single-Voxel Proton Magnetic Resonance Spectroscopy of the Thalamus in Idiopathic Epileptic Dogs and in Healthy Control Dogs - Mauri, Nico; Richter, Henning; Steffen, Frank; Zölch, Niklaus; Beckmann, Katrin M. (Frontiers in Veterinary Science, 2022)
The role of Magnetic resonance spectroscopy (MRS) for the investigation of brain metabolites in epileptic syndromes in dogs has not been explored systematically to date. The aim of the present study was to investigate metabolites in the thalamus in dogs affected by idiopathic epilepsy (IE) with and without antiepileptic drug treatment (AEDT), and to compare them to unaffected controls. Our hypothesis is that similar to humans with generalised epilepsy and loss of consciousness, N-acetyl aspartate (NAA) would be reduced, and glutamate-glutamine (Glx) would be increased in treated and untreated IE in comparison to the control group. In this prospective case control study, Border Collies (BC) and Greater Swiss Mountain dogs (GSMD) were divided in three groups: (1) healthy controls, IE with generalised tonic-clonic seizures with (2) and without (3) AEDT. A total of 41 BC and GSMD were included using 3 Tesla single voxel proton MRS of the thalamus (PRESS-localization, shortest TE, TR=2000 ms, NSA=240). After exclusion of 11 dogs, 30 dogs (18 IE and 12 healthy controls) remained available for analysis. Metabolite concentrations were estimated with LCModel using creatine as reference and compared using Kruskal-Wallis and Wilcoxon rank sum test. Kruskal-Wallis test revealed significant differences in the NAA to creatine (p = 0.04) and Glx to creatine (p = 0.03) ratios between the 3 groups. Wilcoxon test further showed significant reduction of the NAA/creatine ratio in idiopathic epileptic dogs under AEDT compared to epileptic dogs without AEDT (p = 0.03) and compared to healthy controls (p = 0.03). In opposite to humans Glx/creatine ratio was significantly reduced in dogs with IE under AEDT compared to epileptic dogs without AEDT (p = 0.03) and controls (p = 0.02). IE without AEDT and healthy controls did not show significant difference, neither in NAA/creatine (p = 0.60), nor in GLX to creatine (p = 0.55) ratio. In conclusion, MRS showed changes in dogs with IE and generalised seizures under AEDT, but not in those without AEDT. Based upon these results, MRS can be considered a useful advanced imaging technique for the evaluation of dogs with IE in the clinical and research setting.